Hubungan antara Terpaan Berita Negatif BPJS Kesehatan di Media Massa dan Intensitas Komunikasi Word of Mouth di Masyarakat dengan Tingkat Kepercayaan Masyarakat pada Kualitas Pelayanan BPJS Kesehatan - Fatma Izzatussayidati; Tandiyo Pradekso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
The efforts that made by the government to resolve the problem of health in Indonesia is not easy because it often gets negative news in various mass media, the news is a bit influential on the level of public confidence to BPJS Health Care's service quality that shown through the many circulation of negative word of mouth. The purpose of this research is to determine the relationship between news exposure and word of mouth intensity with the level of public confidence in BPJS Health Care's service quality. Sampling in this research is purposive sampling. The population in this study were all society in Semarang City who had seen, heard or read negative news about BPJS Health Care and ever talked about service quality of BPJS Health Care. The number of samples researched as many as 100 respondents.Based on the hypothesis conducted using data anlysis Pearson correlation analysis. The results showed that there was a negative correlation between news exposure in mass media and the level of public confidence in BPJS Health Care’s service quality starter with significance value 0,025 (<0,05). The results showed a negative relationship between the news exposure in mass media with the level of public confidence in BPJS Health Care's service quality with a significance value of 0.025 (<0.05) and Pearson correlation value of -0.224. Furthermore, Pearson's correlation test of word of mouth intensity and level of public confidence in BPJS Health Care's service quality showed a negative relationship with significance value of 0.000 (<0.001) and correlation value of -0.426. This means that the more intense word of mouth in society then the public confidence in BPJS Health Care's service quality will be lower. The suggestion that given is to build relationships with the mass media so that the negative issues can be confirmed in advance and not become a bad word of mouth in society.